Investigating the Impact of Accountability, Religiosity, and Waqf Literacy on Community Interest in Cash Waqf - Nurjanah, Suci; Fithria, Annisa (Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
Purpose - According to Government Regulation Number 28 of 1977 Article 1 (1), waqf is a legal act by an individual or legal entity that separates a portion of their wealth in the form of land and dedicates it for worship purposes or other public interests in accordance with Islamic teachings. The potential for waqf in Indonesia is estimated to reach 180 trillion. In 2022, there was an increase amounting to 1.4 trillion rupiah compared to the proceeds from cash waqf from 2018 to 2021, which stood at 855 billion rupiah. This research aims to analyze the impact of accountability, religiosity, and waqf literacy on the cash waqf interest of the community.Method - A sample of 102 respondents was obtained using the convenience sampling technique. The data analysis technique in this study is multiple linear regression analysis.Result - This research yields findings indicating that accountability and religiosity positively and significantly influence the community's interest in participating in cash waqf. Conversely, waqf literacy exhibits an insignificant impact on the community's interest in engaging in cash waqf.Implication - This study uses information collected from muslim communities in Indonesia to assess their interest in cash waqf.Originality - This study provides insights into the significance of accountability disclosure by waqf institutions and the level of religiosity in influencing an individual's interest in engaging in waqf activities. The results of this research can serve as a foundation for academics, waqf institutions, and government entities to enhance waqf literacy among the public. This effort is crucial for the continued growth and optimization of waqf potential in Indonesia.